Dynamics of Nanoparticles in Stagnation Flames - Zhang, Yiyang (Springer Theses, Recognizing Outstanding Ph.D. Research, 2017)
This book studies the collision, coalescence and deposition of nanoparticles in stagnation flames. With the help of synthesis experiments, in-situ laser diagnostics and molecular dynamics simulations, it investigates the growth of nanoparticles in flames and their deposition in boundary layers at a macroscopic flow field scale, as well as particle and molecular scale issues such as the interaction force between particles, how the collision rate is enhanced by attractive forces, and how the nano-scale coalescence process is influenced by the high surface curvature - all of which are crucial to understanding nanoparticle transport phenomena at high temperatures. The book also reports on a novel in-situ laser diagnostics phenomenon called phase-selective laser-induced breakdown spectroscopy and related applications for tracing gas-to-particle transitions and measuring local particle volume fractions in nano-aerosols.